2007
DOI: 10.1109/tcsi.2007.895383
|View full text |Cite
|
Sign up to set email alerts
|

Pinning Complex Networks by a Single Controller

Abstract: Abstract-In this paper, without assuming symmetry, irreducibility, or linearity of the couplings, we prove that a single controller can pin a coupled complex network to a homogenous solution. Sufficient conditions are presented to guarantee the convergence of the pinning process locally and globally. An effective approach to adapt the coupling strength is proposed. Several numerical simulations are given to verify our theoretical analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
561
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 963 publications
(569 citation statements)
references
References 22 publications
7
561
1
Order By: Relevance
“…[6][7][8][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] In particular, the study on controlling the dynamics of a network and guiding it to a desired state, such as, an equilibrium point or a periodic orbit of the network has become an interesting and important direction in this research field. 7,[18][19][20][22][23][24]26,27 It has been revealed that, in the process of controlling various networks, feedback control serves as a simple and effective approach for stabilization and synchronization. However, it is widely believed that it is impossible to add controllers to all nodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] In particular, the study on controlling the dynamics of a network and guiding it to a desired state, such as, an equilibrium point or a periodic orbit of the network has become an interesting and important direction in this research field. 7,[18][19][20][22][23][24]26,27 It has been revealed that, in the process of controlling various networks, feedback control serves as a simple and effective approach for stabilization and synchronization. However, it is widely believed that it is impossible to add controllers to all nodes.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the control cost, some feedback injections may be added to a fraction of network nodes, which is known as pinning control. [17][18][19][20][22][23][24]26,27,33 In Ref. 17, pinning control of spatiotemporal chaos was discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, [9] showed the number of node which should be pinned in a complex network in order to reach synchronization. It can be seen that in [13][14][15][16][17] that pinning adaptive method is very effective for solving synchronization of complex networks. In [16], the authors investigated the synchronization of nonlinearly coupled networks through an innovative local adaptive approach.…”
Section: Introductionmentioning
confidence: 99%
“…It is a phenomenon that has been widely investigated since it was discovered by Pecora and Carroll in 1990 [8]. Many synchronization patterns have been explored (for example, complete synchronization [9][10][11], cluster synchronization [12,13], phase synchronization [14], partial synchronization [15], projective synchronization [16,17]), and synchronization can be achieved by the use of pinning control [18,19], adaptive control [20][21][22], intermittent control [23], impulsive control [24,25], fuzzy control [26], hybrid control [27] or active control [28].…”
Section: Introductionmentioning
confidence: 99%